Period Matrices of Real Riemann Surfaces and Fundamental Domains - Giavedoni, P. (Symmetry, Integrability and Geometry: Methods and Applications, 2013)
For some positive integers g and n we consider a subgroup Gg,n of the 2g-dimensional modular group keeping invariant a certain locus Wg,n in the Siegel upper half plane of degree g. We address the problem of describing a fundamental domain for the modular action of the subgroup on Wg,n. Our motivation comes from geometry: g and n represent the genus and the number of ovals of a generic real Riemann surface of separated type; the locus Wg,n contains the corresponding period matrix computed with respect to some specific basis in the homology. In this paper we formulate a general procedure to solve the problem when g is even and n equals one. For g equal to two or four the explicit calculations are worked out in full detail.